Language Learning Strategies of Japanese Students Joining â€œEnglish Speaking Societyâ€ - Kobayashi, Ryoichiro (Widya Mandala Catholic University Surabaya, 2016)
This research report aims to investigate what sort of factors make Japanese learners of EFL successful, especially in public speaking activities in universities. The present study focuses on university students who are engaged in English speech activities in a student group called the English Speaking Society (E.S.S.), which most of the Japanese university have. The present study identifies what sort of Language Learning Strategies (LLS) Successful Learners (SL) in E.S.S. use. The results show that cognitive, metacognitive and social strategies are used more frequently than the other strategies of Oxford (1990). The discussions are followed by some implications for non-SL to improve their speaking skills